The Relationship between Learning Readiness and Learning Outcomes of Package C Students at PKBM Titian Amanah Kayu Tanam - Elvira Salman, Iza; Syur'aini, Syur'aini (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2024)
The purpose of study is to ascertain how adult student learning outcomes in Indonesian language classes at PKBM Titian Amanah relate to their readiness for learning. Attention, drive, and the growth of personal preparedness are all components of learning readiness. This study employed a correlational research design and a quantitative methodology. The questionnaire measures the level of learning readiness in terms of attention, motivation and development of individual readiness. Findings of this research indicate the learning readiness of adult students Package C program at PKBM Titian Amanah is in the low category, especially in terms of attention and motivation. This is evident from respondents' propensity to select "disagree" option in the questionnaire. However, research also finds a significant relationship between learning readiness and learning outcomes. Students with a higher level of readiness tend to achieve better learning outcomes. Based on the results of this research, there are several recommendations that can be given. First, PKBM Titian Amanah must provide better facilities to increase adult students' learning readiness. Second, tutors must be more creative in using learning media to increase learning motivation. Additionally, future research could explore the relationship between learning readiness and learning outcomes.Keywords: Learning Readiness, Learning Outcomes